Organizing the Peasants: Participation, Organization and the Politics of Development in a Mexican Government Program - Nuijten, Monique (Anthropologica, 2022)
This article discusses some problems with participatory approaches in development thinking. It is argued that external interventions are always embedded within wider fields of power (force fields) and that discourses of "participation" and "grassroots initiatives" cannot change these established power relations. A study is presented of a Mexican government program that used a "bottom-up participatory approach" in order to stimulate ejidos to formulate their own internal ejido rules. It is shown that this program—in which "local organizing capacities" were said to be central elements—did not change the existing force field and only created more room for officials and intermediaries in their negotiations with peasants